Optimizing Bone Health in Duchenne Muscular Dystrophy - Jason L. Buckner; Sasigarn A. Bowden; John D. Mahan (International Journal of Endocrinology)
Duchenne muscular dystrophy (DMD) is an X-linked recessive disorder characterized by progressive muscle weakness, with eventual loss of ambulation and premature death. The approved therapy with corticosteroids improves muscle strength, prolongs ambulation, and maintains pulmonary function. However, the osteoporotic impact of chronic corticosteroid use further impairs the underlying reduced bone mass seen in DMD, leading to increased fragility fractures of long bones and vertebrae. These serious sequelae adversely affect quality of life and can impact survival. The current clinical issues relating to bone health and bone health screening methods in DMD are presented in this review. Diagnostic studies, including biochemical markers of bone turnover and bone mineral density by dual energy X-ray absorptiometry (DXA), as well as spinal imaging using densitometric lateral spinal imaging, and treatment to optimize bone health in patients with DMD are discussed. Treatment with bisphosphonates offers a method to increase bone mass in these children; oral and intravenous bisphosphonates have been used successfully although treatment is typically reserved for children with fractures and/or bone pain with low bone mass by DXA.